Distal radial artery ligation for treatment of steal syndrome associated with radiocephalic arteriovenous fistula. Issue 9 (14th September 2020) - Tolba, Mahmoud; Maresch, Martin; Kamal, Dhafer
Abstract: We present a case of dialysis associated steal syndrome in a hemodialysis patient with left radiocephalic arteriovenous fistula that caused him severe rest pain. Angiography showed retrograde flow from the ulnar artery to the distal radial artery through a hypertrophied palmar arch. The problem was solved by surgical ligation of the distal radial artery leading to complete relief of patient symptoms without any notable complications.